Sistem Pendaftaran Peserta Didik Baru Di SMA Swasta Pabaku Stabat - Meiliyani Br Ginting; Anggi Widiyanti; Asprina Br Surbakti (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
Admission of new students is one of the processes in educational institutions such as schools that are used to select prospective students according to the criteria of the school concerned. This research was conducted at the Private High School of the Panca Abdi Bangsaku Foundation (PABAKU) which still accepts new students manually, that is, by filling out a form using the sheet provided by the committee. In the study, the researcher decided to create a New Student Registration System at PABAKU Stabat Private High School. New Student Registration System will create a website-based information system and use PHP Mysql. so that the mechanism for registering new students will be more optimal, accurate and in a shorter time. The methods used in this research are data collection, observation, interviews, system requirements analysis, system design, database design, and interface design. In conclusion, this research is a new student registration system at PABAKU Private High School will be built using PHP and MYSQL. So that student data processing is more effective and efficient